Validation and pilot test for items of measurement for adoption of facial recognition payment among senior citizens in Tangshan City of China - Zhou, Yuhan; Bohari, Abdul Manaf (International Journal of Innovative Research and Scientific Studies, 2025)
This study develops and validates a measurement scale to assess senior citizens’ intention to adopt facial recognition payment (FRP) in offline settings in Tangshan, China. Building on the Belief-Attitude-Intention framework and an extended Technology-Organization-Environment-Individual model, the research examines eight key factors: convenience, familiarity, social support, perceived privacy risk, trust, satisfaction, technology anxiety, and intention to use. The study employed a rigorous scale development process involving literature review, expert validation, cognitive interviews, and a pilot test (N=101). The final 34-item questionnaire demonstrated high reliability (Cronbach’s α=0.861). The study contributes to the understanding of senior citizens’ technology adoption by providing a validated measurement tool and practical insights for designing age-inclusive fintech solutions.